Generation and analyses of expressed sequence tags from Sargassum polycystum C. agardh (Fucales, ochrophyta) / Sim Mei Chea - Sim , Mei Chea (2016)
Sargassum polycystum C. Agardh is an economically and ecologically important brown seaweed, being one of the main raw materials for the production of alginate in Asian countries with many applications in the food, feed, pharmaceutical and medical industries. However, its entire genome has not been sequenced, and limited resources are available in the GenBank for understanding the molecular mechanisms underlying alginate biosynthesis. In this study, 2577 high-quality expressed sequence tags (ESTs) were generated from the cDNA library derived from pooled RNA isolated from S. polycystum samples. The ESTs were assembled with stringent parameters, resulting in 295 contigs and 1429 singletons, and giving a total of 1724 unigenes. Of all proteins putatively coded by these unigenes, 46.3 % have significant hits to known proteins in the Swiss-Prot database, and 66.2 % showed significant similarity to sequences in the NCBI non-redundant protein database. The unigenes were functionally characterized by Gene Ontology (GO) annotation, in which ~ 40.3 % were classified into one or more GO categories. We identified two unigenes encoding a potential alginate-related enzyme, mannuronan C5-epimerase (MC5E) and two unigenes encoding sulfated fucan-related enzyme, GDP mannose 4,6 dehyratase (GM46D), and GDP-4-keto-6-D-mannose-epimerase-4-reductase (GFS), respectively. Quantitative real-time PCR (RT-qPCR) analysis revealed differential regulation of these four genes in seaweeds collected during rainy and dry seasons. These EST resources provide valuable sequence information for discovering candidate genes related to important agronomic traits of Sargassum, and gene expression profiling analyses and functional genomics studies to elucidate their roles. The assembly and associated information provides a framework for future investigations in functional genomics in Sargassum species.